Antagonist Test of Trichoderma sp and Gliocladium sp Againts Fungal Pathogens That Cause Diseases on Tomato Plant - Sopialena, Sopialena; Arwita, Nanda Nadira Putri; Suyadi, Suyadi (Jurnal Agroekoteknologi Tropika Lembab, 2024)
Tomatoes (Solanum lycopersicum) are one of the widely cultivated crops consumed by people worldwide, including Indonesia. Tomato farming often faces various challenges that result in reduced tomato productivity. One of the challenges is the presence of diseases that affect tomatoes, leading to crop failure for farmers. Some important diseases that commonly affect tomato plants include Fusarium wilt and anthracnose. Most farmer use chemical fungicides to control the diseases. These methods have greater negative impacts on both plants and the surrounding environment. One alternative control technique that can be used is the use of biological agents with antagonistic properties, such as Trichoderma sp. and Gliocladium sp. This research aims to assess antagonistic abilities of endophytic fungi Trichoderma sp. and Gliocladium sp. againts the pathogens responsible for suppresing the growth of these disease-causing phatogens in tomato plants. in the Laboratory of Plant Pest and Disease Science, OECF Building, Faculty of Agriculture, Universitas Mulawarman. The experiment was designed using a completely randomized single-factor design with four treatments and five replications. The data obtained were analyzed using Analysis of Variance and the least significant difference test at a 5% significance level. The research results indicate that the antagonistic tests of Trichoderma sp. and Gliocladium sp. in vitro significantly differ againts the pathogenic fungi Fusarium sp. and Colletotrichum sp. Furthermore, it was found that the antagonistic fungus Gliocladium sp. is the best fungus capable of suppressing the growth of important pathogenic fungi in tomato plants.Keyword: Gliocladium sp., Trichoderma sp., Fusarium sp., Colletotrichum sp. and Tomato (Solanum lycopersicum)